Preventing child unintentional injury deaths: prioritising the response to the New Zealand Child and Adolescent Injury Report Card. (5th September 2013) - Shepherd, Mike; Kool, Bridget; Ameratunga, Shanthi; Bland, Victoria; Hassall, Ian; Chambers, Julie; Carter, Wayne; Dalziel, Stuart
Abstract Objective: To develop recommendations for child unintentional injury prevention by comparing New Zealand's child unintentional injury mortality and injury prevention policies with those of European countries. Methods: Unintentional child injury death rates based on external cause of injury were calculated and ranked. NZ's score for each of the 12 domains (based on external causes of injury) from the New Zealand Child and Adolescent Report Card was compared to European scoring. Policy priorities are identified by domains where mortality makes up a high proportion of overall child unintentional injury mortality (high burden of injury) and where report card score for that domain is low in comparison to other countries (under‐utilisation of effective interventions). Results: Death as a motor vehicle occupant accounts for 49% of all child unintentional injury deaths, followed by pedestrian (10%) and drowning deaths (8%). The overall score for the 12 policy domains of the NZ Report Card ranks NZ as 15th among the 25 European countries. There are important policy and legislative actions which NZ has not implemented. Conclusions: A number of evidence‐based injury prevention policy and legislative actions are available that could target areas of greatest childhood injury mortality in NZ. Implications: A set of injury prevention policy and legislation priorities are presented which, if implemented, would result in a significant reduction in the injury mortality and morbidity rates of NZ children.